2014
DOI: 10.1002/ejlt.201400309
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes during the frozen storage of the crustacean lobster krill (Munida spp.)

Abstract: This study focused on the quality changes of an undervalorised and underutilised crustacean, lobster krill (Munida spp.) during its frozen storage (10 months at −18°C). Fresh lobster krill specimens were previously soaked in aq. 0.75 and 0.25% sodium metabisulphite (SMB) solutions (0.75‐SMB and 0.25‐SMB conditions, respectively). Comparisons with individuals soaked in water (water control, WC condition) and unsoaked (blank control, BC condition) were carried out. Better sensory acceptance (namely, external col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
10
1
Order By: Relevance
“…This indicated that the lower temperatures could protect mud shrimp from lipid oxidation. García-Soto et al [31] also reported a same trend of FCs development in crustacean lobster krill during frozen storage at −18°C.…”
Section: Formation Of Fcsmentioning
confidence: 54%
“…This indicated that the lower temperatures could protect mud shrimp from lipid oxidation. García-Soto et al [31] also reported a same trend of FCs development in crustacean lobster krill during frozen storage at −18°C.…”
Section: Formation Of Fcsmentioning
confidence: 54%
“…The fatty acid composition of the CLO was analyzed in samples corresponding to days 16 and 30 of storage at 50°C. For it, oils were converted into FAME with acetyl chloride and analyzed by gas liquid chromatography (Perkin‐Elmer 8700 chromatograph, Waltham, MA, USA), employing a fused silica capillary column SP‐2330 (0.25 mm id × 30 m, Supelco Inc., Bellefonte, PA, USA) . The temperature program was as follows: (i) increased from 145 to 190°C at 1.0°C/min; (ii) from 190 to 210°C at 5.0°C/min; and (iii) held for 13.5 min at 210°C.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid content (%) ( Table 1) ranged from 0.75±0.08 (summer) to 0.92±0.06 (winter), so that higher values than those previously reported for this marine product were obtained (García-Soto et al, 2015a, 2015b. This lipid content is also higher than those determined in other crustacean species such as Norwegian lobster (Nephrops norvegicus) (0.70 %; Tsape et al, 2010), pink shrimp (Parapenaeus longirostris) (0.35 %; Cadun et al, 2005), shrimp (0.36 %; Penaeus brasiliensis), crab (0.49 %; Ucides cordatus) and lobster (0.66 %; Panulirus argus) (Pedrosa and Cozzolino, 2001).…”
Section: Chemical Compositionmentioning
confidence: 60%
“…Concerning previous technological studies, Munida spp. have shown a promising behaviour under chilling (García-Soto et al, 2015a) and frozen (García-Soto et al, 2015b) storage. Additionally, recent studies on their carotenoid composition (García-López et al, 2016) and proteolytic activity (D'Ambrosio et al, 2003) have opened the way to other issues of technological interest.…”
Section: Introductionmentioning
confidence: 99%